2019
DOI: 10.12659/msm.919796
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Decompression Attenuates Brain Injury in a Novel Rabbit Model of Acute Intracranial Hypertension

Abstract: This work was supported by Key Disciplines of Wuxi (ZDXK005) and Major Projects of Wuxi Health and Family Planning Commission (Z201705) Background: In the past, standard rapid decompressive craniectomy was used to alleviate the secondary damage caused by high intracranial pressure. Recent clinical studies showed that controlled decompression may have a better curative effect than rapid decompression. However, the effect on controlled decompression in animals is unclear. Material/Methods: Totally 80 healthy mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…4,5 Surgery is indicated for AEDH when it causes a significant mass effect. 6 In this respect, hematoma evacuation by craniotomy can achieve better results. 6 However, surgical treatment for AEDH typically involves craniotomy and must be performed under general anesthesia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4,5 Surgery is indicated for AEDH when it causes a significant mass effect. 6 In this respect, hematoma evacuation by craniotomy can achieve better results. 6 However, surgical treatment for AEDH typically involves craniotomy and must be performed under general anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…6 In this respect, hematoma evacuation by craniotomy can achieve better results. 6 However, surgical treatment for AEDH typically involves craniotomy and must be performed under general anesthesia. This approach can lead to potential complications, such as increased blood loss during surgery and infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The protocol of intracranial hypertension model rabbit was described as a previous study 16 . After 12 h of fasting, the rabbits were anesthetized with intramuscular ketamine (50 mg·kg –1 ), and continuous intravenous infusion of sodium pentobarbital (10 mg·kg –1 ·h –1 ) via the marginal ear vein throughout the remainder of the experiment.…”
Section: Methodsmentioning
confidence: 99%
“…However, the standard procedure of rapid decompression is associated with many postoperative complications, such as delayed intracranial hematoma and diffuse brain swelling [2,3]. Our previous studies have demonstrated that the controlled decompression (CDC) surgery attenuates brain injury and reduces the rates of complications after TBI [4][5][6]. However, the underlying molecular mechanism has not been determined.…”
Section: Introductionmentioning
confidence: 99%